Studi Pemanfaatan Serbuk Gergaji Kayu Mahoni sebagai Campuran Agregat Halus terhadap Sifat Material Batako - Nurma; I Gede Utama Hadi Sutrisna; Ni Putu Ety Lismaya Dew (Mataram University, 2026)
The utilization of mahogany sawdust waste as an additive in concrete blocks production serves as an effort to reduce environmental pollution while providing a more eco-friendly alternative building material. This study aims to analyze the effect of adding mahogany sawdust on the compressive strength of concrete blocks and to assess their conformity with the quality standards of SNI 03-0349-1989. The research was conducted experimentally using sawdust variations of 0%, 1%, 3%, and 5% of the fine aggregate weight, with cube specimens measuring 15 × 15 × 15 cm tested at 28 days. The results show that the addition of sawdust decreases both the weight and compressive strength of the blocks, where the normal block reached a compressive strength of 10.92 MPa, which then dropped to 4.88 MPa at 1%, 3.29 MPa at 3%, and 1.56 MPa at 5% variation. This reduction is caused by the porous and lightweight characteristics of sawdust, along with its high water absorption, which inhibits cement hydration and reduces the density of the block structure. Based on SNI standards, none of the variations met Quality Grade I, however, the 1% and 3% mixtures still fall within Quality Grades III and IV. Overall, mahogany sawdust can be utilized as an environmentally friendly additive for non-structural concrete block applications, but it is not recommended for uses requiring high compressive strength.